Health Bias in Clinical Work with Older Adult Clients: The Relation with Ageism and Aging Anxiety. Issue 2 (15th March 2022) - Caskie, Grace I. L.; Patterson, Shannon L.; Voelkner, Abigail R.
ABSTRACT: Objectives: This experimental study examined health bias in mental health trainees' ratings of work with an older adult client and whether differences based on health were moderated by aging anxiety and ageist attitudes. Methods: Graduate-level mental health trainees ( N = 488) were randomly assigned to read a vignette of an older adult client in good health or poor health, after which they rated aspects of clinical work with this client and completed measures of aging anxiety and ageist attitudes. Results: Trainees rated clinical work with the unhealthy older adult client more negatively than with the healthy older adult client. Health-based differences were larger at average and higher levels of ageist attitudes when considering the appropriateness of the client for therapy and at average and higher levels of aging anxiety for perceived competence to treat and comfort in treating the presenting complaint. Conclusions: Trainees' health bias toward older adults may be magnified by higher aging anxiety and ageist attitudes. Training programs' intervention on these variables may improve geropsychological competencies of future mental health professionals. Clinical Implications: Quality of mental health care for older adult clients may be compromised when biases about older adults, particularly those in poor health, are not addressed.